Temporal variation in memory tests performance in cerebral vascular disease patients / Variação temporal no desempenho em testes de memória em pacientes com doença vascular cerebral - Tania Fernandes Campos; Damião Ernane de Souza; Carolina Dutra Gomes Pinheiro; Alexandre Augusto de Lara Menezes (Psicologia: Reflexão e Crítica, 2007)
This study intended to investigate the performance in memory tests in order to adequate the neuropsychological evaluation to the temporal order of the human organism. Twelve cerebral vascular accident patients and 12 controls, of both sexes and 45-65 years old were studied. Two memory tests with visual stimuli (pictures) and two with verbal stimuli (words) were applied three times a day (08:00, 10:00 and 12:00 h) during the first week and twice a day (14:00 and 16:00 h) in the second week, during three consecutive days in two consecutive weeks. The patients showed lower scores than control subjects in all applied tests (p<0,05). The greater test sensitivity was at 14:00 h for the free recall test and at 16:00 h for recognition tests. According to these results, it is concluded that neuropsychological evaluations should be conducted preferably in the afternoon, as well for the first evaluation as for the re-evaluations.